Enrichment and exposure assessment of As, Cr and Pb of the soils in the vicinity of Stawell, Victoria, Australia - Noble, R.; Hough, R.; Watkins, Ron (Springer, 2010)
Stawell Gold Mine in NW Victoria, Australia, mines ores that contain large concentrations of As and significant quantities of the metals Pb and Cr. The aim of this research was to understand the dispersion, enrichment and probable exposure of these potentially hazardous elements around the mine site. Fifty-five surface soil samples were collected near the mine (<15 km) and analysed by ICP-MS/OES following bioavailable and four-acid extractions. Soils near the mine show greater concentrations of As, Cr and Pb than those near a regionally determined background. This is attributed to the combination of a natural geochemical halo around mineralization and anthropogenic dispersion due to mining and urbanization. Total As concentrations were between 16 and 946 mg kg−1 near the mine in a regional background of 1–16 mg kg−1. Total Cr concentrations were between 18 and 740 mg kg−1 near the mine in a regional background of 26–143 mg kg−1. Total Pb concentrations were between 12 and 430 mg kg−1 near the mine in a regional background of 9–23 mg kg−1. Dispersion of contaminant elements from the present ore processing is <500 m. The most enriched soils occur close to the town and are unrelated to present mining practices. The bioavailable As, Cr and Pb, soil ingestion rates and Risk Reference Doses were used to estimate health risks. An average toddler (12 kg) would need to consume at least 1.5 g, and most likely 12 g, of soil per day to show some symptoms of As toxicity. The maximum measured bioavailable As would pose a risk at average ingestion rates of 200 mg per day. Individuals with soil-eating disorders would exceed the safe daily consumption limits for As, and potentially Cr and Pb. Small children are not typically exposed to soil everyday, very few have soil eating disorders, and, therefore, the health risk from the soils around the mine is minimal.